Pengaruh Pengeluaran Pemerintah Dan Tingkat Pengangguran Terbuka (TPT) Terhadap Pertumbuhan Ekonomi Inklusif Indonesia - Silvi Dewi Purwanti; Farida Rahmawati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
This research is motivated by economic growth, a goal for a country supported by economic development. However, economic growth in Indonesia during the years 2010-2019 has not shown an ever-increasing result at the national level, and poverty and inequality have not been able to decrease. This condition is contrary to the goal of achieving inclusive economic growth. This study aims to measure and analyze Inclusive Economic Growth and the factors that influence it. This study uses two analysis methods: the Poverty-Equivalent Growth Rate (PEGR) model analysis and multiple linear regression analysis with time-series data. The results show that inclusive economic growth in Indonesia has not been consistent every year in the last decade. The time-series data regression analysis results show that the variables of government spending on education and spending on health have a significant effect on inclusive economic growth. The government expenditure variable in education has an inversely proportional impact on inclusive economic growth, while the open unemployment rate (TPT) variable has no significant effect on inclusive economic growth. Efforts that can be made through government policy implications are strengthening the Smart Indonesia Program (PIP) to vocational education. Health facilities, health programs through additional facilities, recruitment of medical personnel to maximize health Indonesia cards, and BPJS.